Vernacular visionaries : international outsider art / edited by Annie Carlano. - Carlanno, Annie (Yale University Press, 2003)
Catalogue of the exhibition on Outsider Art at the Museum of International Folk Art, Santa Fe, October 31, 2003 to summer 2004.